Multinational Factoryless Goods Producers and Expansion of the Wholesale & Retail Industry in Korea. Issue 4 (2nd October 2022) - Hur, Jung; Yoon, Jin Young
Abstract : This paper studies the role of Multinational Factoryless Goods Producers (MFGPs) in the recent expansion of the wholesale and retail industries in Korea. We empirically investigate the impacts of the industry-level store entry rate of the MFGPs on labor productivity growth and store-entry and exit probabilities of Non-MFGPs which are the majority of firms in the industries. Our main results are as follows. First, the industry-level store entry rates of MFGPs are positively associated with increases in labor productivity growth of Non-MFGPs. Second, the industry-level store entry rates of MFGPs are positively related to the store-entry decision of Non-MFGPs. These findings may imply that the entries of MFGP stores contribute to the growth and expansion of the wholesale and retail industries as a whole.